Variable Bone Density of Scaphoid: Importance of Subchondral Screw Placement - Swanstrom, Morgan M.; Morse, Kyle W.; Lipman, Joseph D.; Hearns, Krystle A.; Carlson, Michelle G. (Journal of Wrist Surgery, 2018)
Background Ideal internal fixation of the scaphoid relies on adequate bone stock for screw purchase; so, knowledge of regional bone density of the scaphoid is crucial.Questions/Purpose The purpose of this study was to evaluate regional variations in scaphoid bone density.Materials and Methods Three-dimensional CT models of fractured scaphoids were created and sectioned into proximal/distal segments and then into quadrants (volar/dorsal/radial/ulnar). Concentric shells in the proximal and distal pole were constructed in 2-mm increments moving from exterior to interior. Bone density was measured in Hounsfield units (HU).Results Bone density of the distal scaphoid (453.2 ± 70.8 HU) was less than the proximal scaphoid (619.8 ± 124.2 HU). There was no difference in bone density between the four quadrants in either pole. In both the poles, the first subchondral shell was the densest. In both the proximal and distal poles, bone density decreased significantly in all three deeper shells.Conclusion The proximal scaphoid had a greater density than the distal scaphoid. Within the poles, there was no difference in bone density between the quadrants. The subchondral 2-mm shell had the greatest density. Bone density dropped off significantly between the first and second shell in both the proximal and distal scaphoids.Clinical Relevance In scaphoid fracture ORIF, optimal screw placement engages the subchondral 2-mm shell, especially in the distal pole, which has an overall lower bone density, and the second shell has only two-third the density of the first shell.
Keywords: scaphoid; bone density; subchondral; Hounsfield units